2023
DOI: 10.1021/acsami.3c04022
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Demonstration of Fast Anhydrous Proton Conduction on Graphanol

Abstract: Development of new materials capable of conducting protons in the absence of water is crucial for improving the performance, reducing the cost, and extending the operating conditions for proton exchange membrane fuel cells. We present detailed atomistic simulations showing that graphanol (hydroxylated graphane) will conduct protons anhydrously with very low diffusion barriers. We developed a deep learning potential (DP) for graphanol that has near-density functional theory accuracy but requires a very small fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…It has been shown that graphanol is a promising material for use in proton exchange membrane fuel cells [ 21 , 22 , 32 , 33 ]. As such, graphanol may either be neutral or positively charged due to the addition of protons.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that graphanol is a promising material for use in proton exchange membrane fuel cells [ 21 , 22 , 32 , 33 ]. As such, graphanol may either be neutral or positively charged due to the addition of protons.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The system that we considered is c24C graphanol, as shown in Figure 6 a, which contains a single added proton to one side of the material. We generated a series of 21,400 configurations from a deep learning atomistic potential classical MD simulation [ 21 ]. For each of these configurations, we obtained based on .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1–6 In particular, solid-state proton conductors (SSPCs), as an important component of PEMFCs with broad applications from portable devices to vehicles, can transform chemical energy into electrical energy and have received significant attention. 7–10 Commercial Nafion membranes can achieve a high conductivity of 10 −1 –10 −2 S cm −1 , exhibit excellent chemical stability under mild conditions (98% RH and 60–80 °C), and have become the most widely used proton conducting materials in the market. 11–14 However, poor working conditions ( e.g.…”
Section: Introductionmentioning
confidence: 99%